Traumatic Pictures and Ethical Presentation of Children: A Critical Inquiry on Kunda Dixit’s a People War (Images of Nepal Conflict 1996-2006) - Bhattarai, Krishna Prasad (Butwal Campus Journal, 2023)
The present research takes Kunda Dixit's picture collection A People War (Images of Nepal Conflict 1996-2006) to reveal the pathetic condition of war-affected children. Dixit in this collection demonstrates the stories of those years in pictures. Some of the pictures in this text demonize the Maoist side. This paper argues that the representation of the civil war trauma by Kunda Dixit follows the ethical line while presenting the agony, stress, and disorder of war-affected children. The play of ethical relations creates a prose of otherness towards the perpetrators of the violence condemning the victimizers rather than the act of violence. All the selected pictures are analyzed through trauma theory.